Neuroprotective Effect of IRL-1620, an Endothelin B Receptor Agonist, on a Pediatric Rat Model of Middle Cerebral Artery Occlusion - Cifuentes, Enrique G.; Hornick, Mary G.; Havalad, Suresh; Donovan, Ramona L.; Gulati, Anil (Frontiers in Pediatrics, 2018)
Abstract Objective: The purpose of this study was to determine the potential neuroprotective effect of endothelin B (ETB) receptor agonist IRL-1620 treatment in a pediatric model of ischemic stroke. Design: A prospective, animal model study. Setting: An experimental laboratory. Subjects: Three-month-old male Wistar Han rats. Interventions: The rats underwent permanent middle cerebral artery occlusion (MCAO). At 2, 4, and 6 hours post MCAO, they were treated with saline, IRL-1620 (5 µg/kg, IV), and/or ETB antagonist BQ788 (1 mg/kg, IV). Measurements and Main Results: The rats were evaluated over the course of 7 days for neurological and motor deficit, cerebral blood flow (CBF), and infarct volume. Young rats treated with IRL-1620 following MCAO improved significantly in neurological and motor assessments as compared to the vehicle-treated group, as measured by neurological score (P=0.00188), grip test (P<0.0001), and foot-fault error (P=0.0075). CBF in the infarcted hemisphere decreased by 45-50% in all groups immediately following MCAO. After 7 days, CBF in the infarcted hemisphere of the IRL-1620 group increased significantly (P=0.0007) when compared to the vehicle-treated group (+2.3±23.3% vs. -45.4±10.2%). Additionally, infarct volume was significantly reduced in IRL-1620-treated rats as compared to vehicle-treated rats (P=0.0035, 41.4±35.4 mm3 vs. 115.4±40.9 mm3). Treatment with BQ788 blocked the effects of IRL-1620. Conclusions: IRL-1620 significantly reduced neurological and motor deficit as well as infarct volume while increasing CBF in a pediatric rat model of cerebral ischemia. These results indicate that selective ETB receptor stimulation may provide a novel therapeutic strategy in the treatment of pediatric ischemic stroke as has been demonstrated in adult ischemic stroke.